How Breastfeeding Behavior is Affected by the Breastfeeding Perspectives of Fathers in Georgia (USA) - Les'Shon Irby; Emily Graybill; Cassandra White (Georgia Southern University, 2019)
Background: Father support has recently been associated with increasing breastfeeding rates, but research is limited on how the American father's perspectives of breastfeeding influence breastfeeding behavior. The aim of the study was to investigate the perspectives of fathers residing in Georgia on breastfeeding and to understand if it contributed to mothers' decisions to breastfeed. Methods: We conducted 10 semi-structured, in-depth interviews with parents of ever-breastfeed infants who were at least six months of age. Results: Mothers often led the decision-making process to breastfeed based on her prepartum knowledge of breastfeeding. Many fathers had no prepartum opinion on breastfeeding, and their lack of opinion was not a determining factor in a mother's decision to initiate and continue exclusive breastfeeding. Fathers generally developed a favorable opinion of breastfeeding due to the perceived benefits their child(ren) received. Data also suggested that reasons for supplementing or transitioning to formula were not associated with the father's perspective of breastfeeding. Conclusions: Although the father's perspective on breastfeeding had minimal impact on the mother's decision to breastfeed, having the father's support during breastfeeding aided mothers on their breastfeeding journey and with everyday care taking. Keywords: Breastfeeding behavior, breastfeeding support, exclusive breastfeeding, father, qualitative methods